Analysis of Kaizen Implementation on Production Lead Time and its Impact on Forecast Fulfillment and Production Cost of Film Coated Tablets at PT Z - Sari, Intan Fikri Purnama; Sitanggang, Maura Linda; Widyastuti, Sri (PROMOTOR, 2025)
In the highly competitive pharmaceutical industry, the success of manufacturing companies depends largely on their ability to meet consumer demand on time. However, many companies struggle to achieve their production lead time targets. PT Z, for instance, experiences high lead time during the tablet coating process, leading to failure in fulfilling forecasted demands and increased production costs. This study applies the Kaizen concept, which emphasizes continuous improvement, to enhance production efficiency. The objective is to analyze the effect of Kaizen implementation on production lead time and its subsequent impact on forecast fulfillment and production costs for film-coated tablets. A fishbone diagram was utilized to identify the root causes of the prolonged lead time. The research employed purposive sampling, selecting three film-coated tablet products based on Pareto analysis, with three batches observed for each product. Data were collected through direct observation and Tenaga Kerja Langsung (direct labor) forms. Linear regression was used to determine the relationship between variables, and a paired sample T-test was conducted to assess differences before and after Kaizen implementation. Statistical analysis was performed using SPSS. The findings indicate that Kaizen implementation significantly reduced production lead time, resulting in a decrease in the lead time for film-coated tablets from 31.28 days to 27.66 days. This reduction led to an increase in forecast fulfillment from 93.72% to 127.55% and a decrease in production costs by 35.78%. In conclusion, the application of the Kaizen method effectively shortens production lead time and positively impacts order fulfillment and cost efficiency in film-coated tablet manufacturing.